2021
DOI: 10.1371/journal.pone.0258294
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related institutional betrayal associated with trauma symptoms among undergraduate students

Abstract: Individuals are dependent on institutions (e.g., universities, governments, healthcare systems) to protect their safety and advocate for their needs. When institutions harm the individuals who depend on them, they commit institutional betrayal, which has been associated with numerous negative outcomes in prior research. Throughout the COVID-19 pandemic, students have entrusted universities to protect both their health and their educational opportunities. However, many universities have failed to meet these exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The authors noted that institutional betrayal did not moderate the association between high-school gender harassment and PTSD symptoms; rather, institutional betrayal showed a main effect on trauma symptoms, with a similar effect size as noted in the current study. Additionally, like previous studies with undergraduates (Adams-Clark & Freyd, 2021) and community participants (Bachem et al, 2020), institutional betrayal showed significant associations with negative mental health in this sample of nurses, despite different foci of institutional betrayal. It is clear that the perception an institution is breaking the trust of people who depend on it is associated with increases in mental health symptoms.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The authors noted that institutional betrayal did not moderate the association between high-school gender harassment and PTSD symptoms; rather, institutional betrayal showed a main effect on trauma symptoms, with a similar effect size as noted in the current study. Additionally, like previous studies with undergraduates (Adams-Clark & Freyd, 2021) and community participants (Bachem et al, 2020), institutional betrayal showed significant associations with negative mental health in this sample of nurses, despite different foci of institutional betrayal. It is clear that the perception an institution is breaking the trust of people who depend on it is associated with increases in mental health symptoms.…”
Section: Discussionsupporting
confidence: 83%
“…Two quantitative studies have explored the salience of institutional betrayal during the pandemic. Adams‐Clark and Freyd (2021) surveyed U.S. undergraduate students about their perceptions of COVID‐19–related betrayal by the university they were attending. Over 50% of two separate samples endorsed statements indicating institutional betrayal, such as perceptions that the university created an environment where safety violations were normalized or covered up instances of viral transmission.…”
mentioning
confidence: 99%
“…Furthermore, although research has discussed relationships between perceived stress, cognitions, and coping, few have assessed the relationship all three have among first responders (Beer & Moneta, 2012; Spada et al, 2008). The same can be said about the relationship between perceived stress and IPV myth belief or institutional betrayal, with even fewer studies incorporating cognitions in these relationships (Adams-Clark & Freyd, 2021; Garey et al, 2016; Rovira et al, 2022). Our research question asks if posttraumatic cognitions (self, world, and self-blame) mediate the relationship between perceived stress because of the COVID-19 pandemic and both coping behaviors (healthy and unhealthy) and attitudes (regarding domestic violence and institutional betrayal).…”
Section: Posttraumatic Cognitionsmentioning
confidence: 99%
“…Theoretical work and empirical research have applied this concept to a wide range of institutions and topics, including responses from the U.S. government, universities, and the healthcare industry regarding COVID-19 (Adams-Clark & Freyd, 2021; DePrince & Cook, 2020; Klest et al, 2020), experiences of police brutality (McAuliffe, 2018), racial discrimination in the workplace (Gómez, 2015), among others. The bulk of work, however, has examined the impact of institutional betrayal in the context of sexual trauma across multiple settings (e.g., universities, military service, the court system, churches) (e.g., Andresen et al, 2019; Cook & Freyd, 2019; Smith & Freyd, 2013; Smith et al, 2014).…”
Section: Institutional Betrayalmentioning
confidence: 99%